Study on Lattice and Electronic Structures at the Surface of BaTiO3 Thin Films by DFT Method - Chinh, Nguyen Van; Cong, Bach Thanh; Linh, Nguyen Hoang (Communications in Physics, 2011)
In this paper, the density functional theory (DFT) study on nano-thin films of the most typical ferroelectric compound BaTiO_3 was presented. The results showed that the convergence of the film model using for DFT calculation were obtained for the thickness of the vacuum slabs as large as ten times of the BaTiO_3 slabs within the total energy error 0.01 eV. The lattice contraction was observed in the surface region of the material. The difference in atomic layer termination, between BaO terminated and TiO_2 terminated films, gives rise to the difference in lattice reconstruction at the surface region which, in turn, leads to the difference in surface electric dipoles. The surface effect acts on the electronic structure of thin films in the manner of the asymmetry of atomic sites and the structural reconstruction due to the surface relaxation. Our results indicated that the termination also decides how and how much these two manners take effects on the electronic structure of the material.